BETWEEN REALITY AND IDEALISM: DOES NOVEL READING GENERATE EMPATHY IN ALGERIAN EFL STUDENTS? - Samya Achiri; Fadhila Hadjeris (University of Kuningan, 2016)
This study is an exploration of the extent to which reading novels develops Algerian EFL students’ empathetic attitudes towards human issues in the novel they are exposed to on the one hand and towards current local and worldwide issues on the other. To achieve this aim, a survey questionnaire is designed. The respondents are 50 MA students of Anglo-American Studies at the English Department of Oum El Bouaghi University (Algeria). The students have been exposed to Mark Twain’s The Adventures of Huckleberry Finn as a part of their syllabus. Accordingly, their reactions to the questions concerning this novel provide the necessary data around which this study hinges. The findings of the research are meant to help teachers and researchers to seek out new possibilities of developing more effective ways of using novel reading in EFL university classes. Additionally, the results serve to raise Algerian EFL students’ awareness about reading novels and their impact on stimulating their imagination, critical thinking and emotional attitudes.Keywords: EFL teaching/ learning, novel, narrative empathy, empathetic attitudes, critical thinking, Algeria.